Using Electron Microscopy to Detect SARS-CoV-2 in Human and Animal Tissues. (March 2022) - Bullock, H.; Goldsmith, C.; Ritter, J.; Marines, R.
Abstract : Purpose: Global efforts to combat the COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have placed renewed focus on the use of transmission electron microscopy (EM) for infectious disease diagnosis and detection. Recently, attempts to identify SARS-CoV-2 directly in human autopsy and animal necropsy tissues have inaccurately identified normal subcellular structures, including coated vesicles, multivesicular bodies, and rough endoplasmic reticulum, as coronavirus particles. Working with SARS-CoV-2 positive autopsy and necropsy tissues, the Infectious Diseases Pathology Branch at CDC sought to use EM to accurately detect coronavirus particles. Methods & Materials: Two sample types were used, formalin-fixed wet tissue and formalin-fixed paraffin embedded (FFPE) tissue blocks. Wet tissue samples provide the best preservation of ultrastructure but require a time-intensive search for viral particles. FFPE tissues enable a targeted approach to finding viral particles but with deteriorated ultrastructure. Areas of formalin-fixed wet tissue showing evident disease pathology were selected for EM, while areas of interest from FFPE blocks were selected based on results from SARS-CoV-2 immunohistochemistry and in situ hybridization results. All samples were post-fixed with 1% osmium tetroxide, en-bloc stained with uranyl acetate, dehydrated, and embedded in Epon-Araldite resin. Results: A multifaceted approach for SARS-CoV-2 detection in autopsy and necropsy tissues allowed for swift and accurate determination of the localization of coronavirus and correlation of histopathological and ultrastructural features of SARS-CoV-2 infection. Coronavirus particles were found associated with degenerating cells in the alveolar space, in pneumocytes, and near collagen of the heart in fetal tissue as well as in the syncytiotrophoblast of the placenta. In animal tissues, virus was found in the bronchiolar epithelium and type 1 pneumocytes. Conclusion: Comprehensive studies of SARS-CoV-2 infection, and all emerging pathogens, are crucial to improving the understanding of pathogenesis and for the formulation of clinical treatments and transmission prevention measures. An important part of this process is providing robust EM evidence of SARS-CoV-2 localization within tissues to ensure that misinterpretations of subcellular structures as virus are reduced, enabling more accurate conclusions concerning COVID-19 pathology and disease.